HUBUNGAN MENGKONSUMSI KOPI DAN MEROKOK DENGAN TERJADINYA INSOMNIA PADA LANSIA DI WILAYAH KERJA UPT PUSKESMAS SEI LANGKAI KOTA BATAM - Nur Mastari; Savitri Gemini; Desy Desy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The prevalence of elderly people experiencing insomnia every year is estimated at around 25%-57% and 19% experience serious sleep disorders. As they age, the elderly usually face various health problems, one of which is insomnia. This insomnia not only worsens the quality of life of the elderly, but also increases the possibility of health complications such as hypertension, stroke, coronary heart disease, and even the risk of premature death. One of the contributing factors is excessive coffee consumption and smoking habits. Research Objective To determine the relationship between coffee consumption and smoking with insomnia in the elderly in the Sei Langkai Community Health Center Work Area. This study used an analytical observational design through a Cross Sectional approach. The research sample was 95 elderly people taken using a purposive sampling technique. The data collection tool used a questionnaire and data analysis used the Spearman Rank statistical test. Based on the results of the Spearman Rank statistical test on the relationship between coffee consumption and smoking, the p-value showed 0.000 (0.05) which means Ho was rejected. Therefore, it can be concluded that there is a relationship between coffee consumption and smoking and insomnia in the elderly in the Sei Langkai Community Health Center (UPT) working area of Batam City. Elderly people should reduce excessive coffee consumption and stop smoking, as both can worsen heart and lung health, sleep problems, and increase the risk of chronic disease. Keywords: Insomnia, Elderly, Coffee Consumption, Smoking